Di-(2-ethylhexyl) phthalate-induced hepatotoxicity exacerbated type 2 diabetes mellitus (T2DM) in female pubertal T2DM mice. (March 2021) - Ding, Yangyang; Xu, Tong; Mao, Guanghua; Chen, Yao; Qiu, Xuchun; Yang, Liuqing; Zhao, Ting; Xu, Xiaoxiao; Feng, Weiwei; Wu, Xiangyang
Abstract: Di-(2-ethylhexyl) phthalate (DEHP), one of the most common plasticizers, is closely associated with a high prevalence of pubertal type 2 diabetes mellitus (T2DM). Numerous studies have indicated that DEHP-induced metabolic toxicity exhibits sex differences. In this study, the sex differences in the effect of DEHP on pubertal T2DM (P-T2DM) mice, the susceptibility of female P-T2DM mice to DEHP-induced metabolic toxicity, and the underlying mechanisms were investigated. DEHP exposure exacerbated metabolic disorders in female P-T2DM mice. Factorial analysis showed that female P-T2DM mice were more sensitive to DEHP exposure than female normal mice and male P-T2DM mice. It was determined by integrated biomarker response results that female P-T2DM mice had higher risks of developing T2DM, metabolic disorders, cardiovascular events and hepatotoxicity than male P-T2DM mice. Moreover, hepatic transcriptome analysis emphasized the effects of DEHP on the expression of oxidative injury- and metabolic function-related genes. Western blotting indicated that DEHP activated Jun-N-terminal kinase (JNK) and impaired insulin sensitivity in the liver, which were the main causes of DEHP-exacerbated metabolic abnormalities in P-T2DM mice. Our study revealed that compared with normal mice and male P-T2DM mice, female P-T2DM mice tend to suffer from increased DEHP-induced metabolic toxicity, which was primarily attributed to hepatotoxicity. Graphical abstract: Fig. The potential mechanism for DEHP induced metabolic toxicity on female P-T2DM miceThis study revealed that DEHP could exacerbate metabolic disorders, cardiovascular risks and the injury of hepatic function in female pubertal T2DM mice. The female P-T2DM mice exposed to DEHP have higher risks of T2DM development than male P-T2DM mice. DEHP exacerbates the metabolic disorders of female T2DM mice by impairing hepatic function. The DEHP-activated JNK and DEHP-induced oxidative injury in the liver are the main causes of DEHP-exacerbated metabolic abnormality in P-T2DM mice, which could further block the insulin signal transduction in female pubertal T2DM mice Image 1 Highlights: DEHP could cause metabolic toxicity in female pubertal mice. Female pubertal T2DM mice are more sensitive to DEHP exposure. Female T2DM mice tend to suffer from DEHP-induced metabolic toxicity. DEHP exacerbates metabolic disorders of female T2DM mice mainly by hepatotoxicity.